Optimization Strategy Utilization Of Zakat In Improving The Welfare Of Mustahik At Baznas Kendari, Southeast Sulawesi - Akhmad Arkal Pratama Akib, Ayu Janianti Yusuf, Muslimin Kara, Amiruddin K., Abdul Wahab (South Eastern European Journal of Public Health, 2025)
Zakat is an important instrument in the Islamic economic system that functions as a means of income redistribution and improving community welfare. However, the effectiveness of zakat is largely determined by its management strategy. This study aims to analyze the zakat utilization optimization strategy implemented by BAZNAS Kendari, assess the effectiveness of this strategy in improving the welfare of mustahik, analyze the impact of implementing the zakat optimization strategy, and formulate priority strategies based on a SWOT analysis. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation of BAZNAS managers, mustahik recipients of productive and consumptive zakat, muzakki, as well as community and religious leaders. Data analysis was carried out using the IFAS, EFAS, SWOT, and Quantitative Strategic Planning Matrix (QSPM) matrices. The results of the study indicate that the zakat optimization strategy at BAZNAS Kendari is directed at strengthening productive zakat, mentoring mustahik businesses, and managing programs based on digitalization needs . This strategy has proven effective in gradually improving the welfare of mustahik in the economic, social, and spiritual aspects, although not all mustahik have experienced the transformation of status into munfiq or muzak k i. The results of the SWOT analysis place BAZNAS Kendari in Quadrant I (aggressive strategy), with the priority strategy being strengthening productive zakat based on intensive mentoring and continuous monitoring. This research provides a practical contribution to regional zakat management and enriches the study of zakat management based on strategic analysis.